Using Data Analytics to Monitor Health Provider Payment Systems: A Toolkit for Countries Working Toward Universal Health Coverage - Fred Adomako-Boateng; Yakubu Agada-Amade; Arturo Clemente Alcantara; Caren Althauser; Edwine W. Barasa; Cheryl Cashin; Vergil Manatad de Claro; Gilda Salvacion Abrenica Diaz; Lydia Dsane-Selby; Stanley Wilson Effah; Fauziah Zainal Ehsan; Mohd Fozl Bin Kamarudin; et al. (Joint Learning Network for Universal Health Coverage (JLN), 2017)
This toolkit seeks to address the gap in data utilization by providing guidance and tools based on practical experience to help countries implement provider payment monitoring systems that use claims and/or other routine administrative data. Such a monitoring system can: 1) generate indicators and analytic reports to monitor whether provider payment systems are achieving service delivery and other objectives or leading to unintended consequences, 2) point to particular services, providers, or other areas that warrant deeper analysis, 3) alert purchasers if modifications to the payment systems design and implementation may be needed, and 4) support ongoing dialogue among purchasers, providers, and other stakeholders that can lead to better health service delivery and help refine provider payment systems.
Keywords: 330; provider payment; data analytics; universal health coverage